(untitled) - Brown, Azby (Tokyo, 1989)
A discourse on the whole traditional building system in Japan. Not a how to book, but certainly with the many illustrations a serious carpenter could gleam some very interesting techniques from the pages.
Keywords: Carpentry,Buddhist temples,Nghề thợ mộc,Đền thờ Phật giáo; Design and construction,Thiết kế và kiến trúc; Japan,Nhật Bản